Acute effects of a single dose of 2 mA of anodal transcranial direct current stimulation over the left dorsolateral prefrontal cortex on executive functions in patients with schizophrenia: a randomized controlled trial - Schilling, Thomas M.; Bossert, Magdalena; Koenig, Miriam; Wirtz, Gustav; Weisbrod, Matthias; Aschenbrenner, Steffen (PLOS ONE, 2021)
Objective Cognitive impairments are a frequent and difficult to treat symptom in patients with schizophrenia and the strongest predictor for a successful reintegration in occupational and everyday life. Recent research suggests transcranial direct current stimulation (tDCS) to enhance cognition in this patient group. However, the question regarding its acute effectiveness on executive functions remains largely unanswered. Here, we examined in a randomized, double blind, sham-controlled repeated-measures design the impact of tDCS on performance in several executive functions in patients with schizophrenia, schizoaffective disorder or acute transient psychotic disorder. Methods Patients (N = 48) were tested twice using standardized, well-constructed and clinically validated neuropsychological tests assessing verbal working memory, response inhibition, mental flexibility and problem solving. In session 1 they solely underwent the neuropsychological assessment, whereas in session 2 they additionally received 2 mA of anodal tDCS stimulation over the left dorsolateral prefrontal cortex (DLPFC), cathode right supraorbital ridge, or sham stimulation for 20 minutes. Results Patients of both groups were not able to correctly discriminate the type of stimulation received confirming the success of the blinding procedure. However, analyzing the whole sample the change in performance from session 1 to session 2 was the same in the verum as in the sham condition (all p >.5). Moreover, a subsequent exploratory analysis showed that performance in the response inhibition task was worse for patients that engaged in the task within 20 minutes after the end of the verum stimulation. Conclusion Hence, 2 mA of anodal tDCS applied over the left DLPFC did not acutely enhance executive functions in patients with schizophrenia or related disorders but impaired performance in the response inhibition task shortly after. Future studies should continue to seek for effective stimulation configurations for this patient group.